Step-by-step explanation:
Input Equation can be rewritten:
= (9*1/2)+(7*-91/12)
= (9/2)+(7*-91/12)
= (4.5)+(7*-91/12)
= 4.5+(7*-91/12)
= 4.5+(-637/12)
= 4.5+(-53.083333333333)
= 4.5+-53.083333333333
= 4.5-53.083333333333
= -48.583333333333
hope this helps!
Answer:
-1/6
Step-by-step explanation:
24x=-4
X=-4/24
X=-2/12
X=-1/6
Answer:
I'm bad at math sorry I need help with social studies. helppppppp
Step-by-step explanation:
HELP
Answer:
m∠ABC = m∠BED; Corresponding Angles Theorem
Step-by-step explanation:
<u>Given:</u> line BC is parallel to line ED m∠ABC = 70° m∠CED = 30°
<u>Prove:</u> m∠BEC = 40°
Statement Justification
1. line BC is parallel to line ED - Given
2. m∠ABC = 70° - Given
3. m∠CED = 30° - Given
4. m∠BEC + m∠CED = m∠BED - Angle Addition Postulate
5. m∠ABC = m∠BED - Corresponding Angles Theorem
6. m∠BEC + 30° = 70° - Substitution Property of Equality
7. m∠BEC = 40° Subtraction Property of Equality